N-{4-[4-(4-Fluorophenyl)-1-(2-methoxyethyl)-2-methylsulfanyl-1H-imidazol-5-yl]-2-pyridyl}-2-methyl-3-phenylpropionamide - Ziegler, Katharina (International Union of Crystallography, 2009)
In the crystal structure of the title compound, C(28)H(29)FN(4)O(2)S, the imidazole ring makes dihedral angles of 11.85 (7), 73.33 (7) and 22.83 (8)° with the 4-fluorophenyl, pyridine and phenyl rings, respectively. The 4-fluorophenyl ring makes dihedral angles of 77.91 (7) and 26.93 (8)° with the pyridine and phenyl rings, respectively. The phenyl and pyridine rings are nearly perpendicular, making a dihedral angle of 86.47 (9)°. The crystal packing shows an intermolecular N—H⋯O hydrogen-bonding interaction between the N—H and carbonyl groups of the amide functions.